PENERAPAN PHET SIMULATIONS DALAM PENINGKATAN PEMAHAMAN KONSEP SISWA PADA MATERI HUKUM NEWTON - Sevina Rizky Octavia, Enny Susiyawati (CV. Adiba Aisha Amira, 2024)
The aim of this research is to describe the effect size of students' conceptual understanding and their responses to the use of PhET Simulations on Newton's Law material at SMP Labschool Unesa 1 Surabaya in the 2023–2024 academic year. With 32 students as a sample, this pre-experimental quantitative-descriptive approach was used. For this research, a one-group pretest-posttest design was used. Data collection techniques consist of tests and questionnaires. The first is used to measure how well students understand concepts about the material, and the second is used to find out how students respond to learning that has been carried out. The Wilcoxon test and effect size were used to assess student understanding. The research results show that understanding the concept of each indicator has an impact of 2,130. In addition, the effect value of each indicator is reviewed. Indicators in the Very Large category interpret and compare, with values of 1.02 and 1.495; indicators in the Large category classify and explain, with values of 0.591 and 0.879; and indicators in the Medium category provide examples, summarize, and draw inferences, with values of 0.354, 0.481, and 0.448. 81% of students responded to the PhET application with the criteria of strongly agreeing. The research results show that students understand the concepts better after using PhET Simulations on Newton's Law material.